Government Expenditure and the Economy: The Nigeria Perspective - , Ugbede Onalo; , Mohd Lizam; , Ahmad Kaseri (Archives of Current Research International, 2016)
Logically, government expenditure is expected to boost economic activities and performance. However, this study conjectured that capital and recurrent expenditure or a combination of both would impact differently on the economy. Thus, this study evaluated whether there is no short run and long run causality running from capital expenditure, recurrent expenditure and aggregate expenditure to gross domestic product. Secondary data used for this study were collected from Central Bank of Nigeria statistical bulletin over a period of 34 years (1981-2014). Stationarity test for variables was performed to establish whether variables are stationary or nonstationary. Johansen cointegration test was employed to investigate whether variables are cointegrated or not. Having established that variables are not cointegrated, VAR Granger Causality model was estimated. Since this study focused on four variables (GDP, CAPE, RECE and TOTE), VAR estimated four linear regressions specifying each of the variables as dependent variable. The second linear regression model where capital expenditure was the dependent variable was the only significant model among all. Essentially, results established significant association between CAPE and GDP lag 1 and GDP lag 2. In other words, GDP lag 1 and GDP lag 2 jointly influences CAPE or CAPE influences GDP lag 1 and GDP lag 2. This outcome has practical implication for Nigeria policy makers and Nigeria government at large. This study therefore recommends a monumental increase in Nigeria capital expenditure as such increase has potentials of propelling economic performance in terms of GDP.